Microbial activity in a semiarid soil cultivated with Atriplex nummularia - Pereira, Sônia Valéria; Martinez, Cosme Rafael; Porto, Everaldo Rocha; Oliveira, Beatriz Regina Brito; Maia, Leonor Costa (Pesquisa Agropecuaria Brasileira, 2004)
Methods used to estimate the soil microbial activity are important to environmental monitoring of degraded areas. The objective of this research was to investigate the microbial activity of a semiarid soil cultivated with Atriplex nummularia Lindl. in a field receiving saline waste during one and three years, in comparison with an area without crop and irrigation. Soil cultivated during three years presented, during the dry season, values of pH, CE, and activity of FDA hydrolyses higher than those registered in other areas. However, a negative correlation between the microbial carbon and values of qCO2 was observed. The microbial biomass and the alkaline phosphates were also higher in the three years cultivated soil, in comparison with the native soil, non irrigated, confirming the role of halophytes for enhancing quality of soils under saline stress. Thus, the cultivation of A. nummularia is an alternative for using saline waste from the desalinization process.